On the origin of the high tensile strength and ductility of additively manufactured 316L stainless steel: Multiscale investigation. (15th March 2020) - Barkia, Bassem; Aubry, Pascal; Haghi-Ashtiani, Paul; Auger, Thierry; Gosmain, Lionel; Schuster, Frédéric; Maskrot, Hicham
Abstract: We report that 316L austenitic stainless steel fabricated by direct laser deposition (DLD), an additive manufacturing (AM) process, have a higher yield strength than that of conventional 316L while keeping high ductility. More interestingly, no clear anisotropy in tensile properties was observed between the building and the scanning direction of the 3D printed steel. Metallographic examination of the as-built parts shows a heterogeneous solidification cellular microstructure. Transmission electron microscopy observations coupled with Energy Dispersive X-ray Spectrometry (EDS) reveal the presence of chemical micro-segregation correlated with high dislocation density at cell boundaries as well as the in-situ formation of well-dispersed oxides and transition-metal-rich precipitates. The hierarchical heterogeneous microstructure in the AM parts induces excellent strength of the 316L stainless steel while the low staking fault energy of the as-built 316L promotes the occurrence of abundant deformation twinning, in the origin of the high ductility of the AM steel. Without additional post-process treatments, the AM 316L proves that it can be used as a structural material or component for repair in mechanical construction.